Patterns of dosage regimen instructions regarding topical medicines: how is the information perceived by patients?. (19th May 2022) - Teixeira, Ana; Teixeira, Maribel; Bento, Carmen; Azevedo, Luís Filipe; Vasconcelos, Viviana; Bahia, Maria Fernanda; Torres, Tiago; Morna, Carla; Castro, Eunice; Vidal, Diogo Guedes; e Sousa, Hélder Fernando Pedrosa; Dinis, Maria Alzira Pimenta; et al.
ABSTARCT: Background: The communication of dosage regimen instructions by physicians is of utmost importance on treatment adherence. Few studies until now have approached the topical treatment adherence subject. Objective: This study aims the characterization of dosage regimen instructions given by physicians and the assessment of chronic dermatological patients' perception regarding these instructions. Methods: Two instruments one for physicians (PHYSDOSAGE) and one for patients (PATIENTDOSAGE) were developed and applied in a cross-sectional, descriptive and exploratory study to two independent samples composed by 91 physicians and 43 patients. Results: Most of physicians reported to provide dosage regimen instructions. When cross checking information from both studied samples, physicians and patients, it was concluded that physicians reported to provide more frequently oral and written treatment instructions, e.g. electronic prescription, than patients reported having received it. Also, physicians claimed to often provide information about the duration of treatment and the frequency of topical medicines' application, which was not acknowledged by patients. Conclusions: Contradictory results were found between the physicians' information input and the patients' perception about dosage regimen instructions provided during the consultation. These findings could negatively influence the treatment adherence and the clinical outcomes. Thus, it is of paramount importance the implementation of strategies to improve optimal communication of dosage regimen instructions for topical medicines.